Ավանդություններ, սովորություններ, պատմական վայրեր - Բաղդասարյան, Սիրուն (ԱրՊՀ հրատ․)
In article is observed and examined the mentions which had taken place in the prose of Khachik Dashtents which told about traditions, habits and historical places. Being the author of historical-saying type Dashtents with his prose was presented as aesthete, who well know described country Sasun and about the talks of their popular names. It is underlined that national traditions, geographical places, sensation, the people views, the protection of nature were different manifestated in the work of Khachik Dashtents. В статье рассматриваются упоминания, которые нашли свое место в прозе Хачика Даштенца, который рассказывает о традициях, обычаях и исторических местах. Будучи писателем исторического типа Даштенц своей прозой представился как эстет, который прекрасно описывает страну Сасун, его разговоры и его знаменитые имена. Подчеркивается, что национальные традиции, места, чувства и взгляды людей, защита природы по разному отражаются в работе Даштенца.
Keywords: Բանահյուսություն; Ազգագրություն